2007
DOI: 10.1002/rob.20222
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive teams of autonomous aerial and ground robots for situational awareness

Abstract: In this paper, we present the component technologies and the integration of these technologies for the development of an adaptive system of heterogeneous robots for urban surveillance. In our integrated experiment and demonstration, aerial robots generate maps that are used to design navigation controllers and plan missions for the team. A team of ground robots constructs a radio signal strength map that is used as an aid for planning missions. Multiple robots are to establish a mobile, ad-hoc communication ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 35 publications
0
63
0
Order By: Relevance
“…This work opens up the possibility of distributed sensors being used both for acquiring information and providing state information for controlling individual vehicles. Coordination of ground and air vehicles is discussed by Hsieh et al (2007) where benefits similar to those found in this work are identified, namely the ability of air vehicles to cover large areas at low resolution relatively rapidly, complements the ability of ground based robots to carry larger sensors to gain more accurate information about specific targets. This paper outlines the structure of the ground and aerial vehicles used to compete in the MOD grand challenge.…”
Section: Introductionmentioning
confidence: 62%
“…This work opens up the possibility of distributed sensors being used both for acquiring information and providing state information for controlling individual vehicles. Coordination of ground and air vehicles is discussed by Hsieh et al (2007) where benefits similar to those found in this work are identified, namely the ability of air vehicles to cover large areas at low resolution relatively rapidly, complements the ability of ground based robots to carry larger sensors to gain more accurate information about specific targets. This paper outlines the structure of the ground and aerial vehicles used to compete in the MOD grand challenge.…”
Section: Introductionmentioning
confidence: 62%
“…In most related works, the aerial robot flies outdoors higher than 20 meters, and can be localized using GPS [7]- [9]. To the best of our knowledge, the work in [1] is the first to demonstrate how a MAV could assist a ground robot in close collaboration in mapping a damaged building indoors.…”
Section: Related Workmentioning
confidence: 99%
“…Hsieh et al [8] deployed multiple UAVs and ground vehicles to locate and track human targets in large indoors and outdoors environments using a Simultaneous Localization and Mapping (SLAM) approach. Their two-phase search process consists of identifying targets visually within a map of the target region, which is constructed from aerial footage obtained using UAVs.…”
Section: Related Workmentioning
confidence: 99%